2017
DOI: 10.3233/jnd-170233
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Skipping of Single Exon Duplications in DMD Patient-Derived Cell Lines Using an Antisense Oligonucleotide Approach

Abstract: This study provides another proof of concept for the feasibility of therapeutic skipping in patients carrying exon duplications in order to express wild-type, full-length mRNA, although careful evaluation of the skipping efficiency should be performed as some exons are easier to skip than others. Such a personalized strategy is expected to be highly beneficial for this subset of DMD patients, compared to inducing expression of an internally-deleted dystrophin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Among our Saudi patients with DMD gene deletions, the exons most frequently skipped were exons 51 (42.9%, 9/21), 53 (14.3%, 3/21), 44 (9.5%, 2/21), 45 (4.8%, 1/21), 43 (4.8%, 1/21), and 50 (4.8%, 1/21). Wein et al have recently reported the efficiency of exon skipping in the DMD gene, with each duplicated exon expressing a wild-type, full-length mRNA [ 66 ]. For more than one duplicated exon, several antisense oligomers can be delivered as a cocktail of drugs to skip larger regions of the transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Among our Saudi patients with DMD gene deletions, the exons most frequently skipped were exons 51 (42.9%, 9/21), 53 (14.3%, 3/21), 44 (9.5%, 2/21), 45 (4.8%, 1/21), 43 (4.8%, 1/21), and 50 (4.8%, 1/21). Wein et al have recently reported the efficiency of exon skipping in the DMD gene, with each duplicated exon expressing a wild-type, full-length mRNA [ 66 ]. For more than one duplicated exon, several antisense oligomers can be delivered as a cocktail of drugs to skip larger regions of the transcript.…”
Section: Discussionmentioning
confidence: 99%
“…However, when skipping is too efficient and both exons are skipped, the reading frame will be disrupted. In cell cultures, generally both exons are skipped [43,44], although for some exons using lower AON doses can increase the amount of single exon skipping [44,45]. It is anticipated that in vivo the efficiency of AON delivery is much more limited and that it is very unlikely that two AONs target the same dystrophin transcript in one nucleus [8].…”
Section: Clinical Development For Small Mutations and Duplicationsmentioning
confidence: 99%
“…AO-mediated exon skipping can correct the reading frame by removing the mutated exon and/or its flanking exon(s) from the DMD pre-mRNA, leading to a truncated but partly functional dystrophin protein, thus producing a milder phenotype as in the case of BMD patients [ 25 ]. In animal and cell models of DMD, exon skipping has been demonstrated to correct deletion, duplication, nonsense, and splice site mutations [ 26 , 27 , 28 , 29 ]. An antisense phosphorodiamidate morpholino oligomer (PMO) targeting exon 51, called eteplirsen or Exondys 51 (Sarepta Therapeutics, Cambridge, MA, USA), was conditionally approved by the Food and Drug Administration (FDA) in 2016, and several PMOs targeting other DMD exons, including golodirsen (SRP-4053) and NS-065/NCNP-01 (NS Pharma, Paramus, NJ, USA) are currently under clinical trials.…”
Section: Exon Skipping Therapy For Dmdmentioning
confidence: 99%